Design and implementation of healthcare biometric systems - Kisku, Dakshina Ranjan; Gupta, Phalguni 1955-; Sing, Jamuna Kanta (IGI Global, 2019)
"This book provides latest developments made in healthcare biometrics and its related areas to ensure exhibiting state-of-the-art technologies. It discusses various issues related to healthcare biometrics and their effective solutions presented in a well-organized manner. It includes cutting-edge biometrics methodologies like template protection, adaptive systems, cohort selection, ensemble systems, deep learning, liveness detection, and cyber-physical biometrics systems"...Provided by publisher